Design and implementation of a neural network in an FPGA for pattern recovery - Morales Villanueva, Aurelio (2007)
This research work shows the design and implementation in hardware based on highly complex programmable logic devices such as FPGAs, of a Hopfield artificial neural network for the recovery of stored patterns from fuzzy patterns. They were designed in artificial neural networks (basic and advanced), using FDA electronic design tools and hardware description language.